ANALISIS SEGMENTASI POST-HOC PELUMAS 4T DAN HUBUNGAN ATRIBUT-ATRIBUT PELUMAS 4T DENGAN KARAKTERISTIK DEMOGRAFI PELANGGAN DI SURABAYA - Jenu Widjaja Tandjung; Armanu Toyib; Multifiah . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2006)
A competition of 4T oil business is growing up. It can be seen from the increasing of a number of producers that have NPT (registered oil number). Customers will have more choices selecting many trademarks of 4T oil. To come out on top of this competition, the oil producers need to know oil attributes that influence customer choosing trademarks of 4T oil.This study wants to know the relationship between customer demography based on age, income, education level, sex and occupation with the choosing of 4T oil attributes. Besides, it is also to know the oil attributes that have strong relationship with characteristics of customer demography. The researcher also wants to know the relationship of customer demography of 4T oil with 4T oil post-hoc segmentation.This study focuses on 4T oil with motorcycle owners who change 4T oil in the garages in city area of Surabaya as samples. In taking sample, rescuer used accidental sampling with 168 people as respondents. Respondent characteristic is limited on demographically characteristic. Besides using primer data, it also used secondary data which taken from tabloid of Marketing, Jawa Pos, Badan Pusat Statistik, Indommercial and Bulletin Dirjen Migas. Scale and measurement that are used in this study is Likert Scale. Whereas, researcher used correlation of Rank Spearman and CHAID (Chi-Square Automatic Interaction Detection) as method of data analysis.The interesting result of this study is the choosing of 4T oil attributes in relation with characteristic of demography that is age, income, education, and occupation. Whereas, sex is not in relation with the choosing of 4T oil attributes. Besides, the customers of 4T oil tend to be rational that is taking more consideration on quality, acceleration of machine and oil endurance comparing with appearance and price.